Molecular diagnosis of haemophilia A: four novel variants identified in five patients - Certã, Rita (2020)
Aims/Context: Haemophilia A (HMA) is an X-linked bleeding disorder caused by reduced levels of the coagulation factor VIII (FVIII) due to alterations in the F8 gene. Decreased levels of FVIII activity leads to a loss of clotting activity and to bleeding (predominantly into joins, muscles and inner organs). The severity of HMA ranges from mild (5-30% activity) to moderate (2-5% activity) to severe (<1% activity). During the last five years, we have found four novel variants identified in five index patients with no family history of HMA. Three frameshift variants were detected in patients presenting severe HMA and one missense variant was identified in two unrelated patients with a mild phenotype. Methods: Analysis of the F8 gene was performed in five index patients using PCR followed by Sanger sequencing, after F8 IVS22 and IVS1 inversions being excluded in severe HMA cases. Bioinformatics analysis was performed with several pathogenicity prediction tools (Alamut Visual, VarSome, VEP and Human Splicing Finder). Results and Conclusions: In the three patients with severe HMA, three different novel F8 variants were identified: c.1060_1061delCT, p.(Leu354Thrfs*5), c.4804delC, p.(Gln602Lysfs*19) and c.3561dupT, p.(Pro1188Serfs*10). All these variants create a frameshift, leading to a premature termination codon and presumably resulting in non-functional truncated proteins, confirming the patient’s phenotypes. The novel F8 missense variant c.5836G>T, p.(Asp1946Tyr) was identified in two unrelated patients, both with mild HMA. The Asp1946 is a highly conserved amino acid in the FVIII protein. Additionally, physicochemical properties between Asp and Tyr are significantly different, and in silico analysis classified it as pathogenic due to the amino acid substitution. Normal mRNA splicing process can also be disturbed due to the creation of a new donor splice site. RNA studies and other functional assays are essential in order to establish this variant clinical significance. Identification of novel pathogenic F8 variants in HMA patients allows genotype-phenotype correlations, appropriate genetic counseling and new knowledge about the molecular bases of this pathology.